Analisis Financial Perfomance dalam Meningkatkan Harga Saham (Studi Keuangan pada Perusahaan yang Tergabung dalam Jakarta Islamic Index Tahun 2017-2021) - Gunawan, Meilani; Jhoansyah, Dicky; Komariah, Kokom (Universitas Batanghari Jambi, 2025)
The purpose of this study is to determine the effect of liquidity ratio, activity ratio, leverage ratio, profitability ratio and market ratio on stock prices in companies included in the Jakarta Islamic Index during the period 2017-2021. The method in this study uses a quantitative descriptive method with a purposive sampling technique. The research analysis uses scale calculations, correlation coefficients, determination coefficients, F tests and t tests. The results of this study indicate that simultaneously there is an influence between financial ratios on stock prices in companies included in the Jakarta Islamic Index, but partially only the profitability ratio and market ratio show a significant influence on increasing the stock price of the Jakarta Islamic Index.